Vous êtes sur la page 1sur 41

SOLVING QUADRATIC

EQUATIONS
Content Standard

The learners demonstrate understanding


on how to solve quadratic equations.
Performance Standard

The learners shall be able to keenly


observe the process or steps on how to
solve quadratic equations.
Learning Competency

The learner will be able to solve quadratic


equation by: (a) extracting square roots;
(b) factoring; (c) completing the square;
(d) using quadratic formula
Objective:
At the end of the session, the learners should
be able:
1. solve the quadratic equations.
2. identify the methods or process on how to
solve quadratic equations.
3. Identify the quadratic equations if it is
complete or incomplete quadratic equations.
A. SOLVING QUADRATIC EQUATIONS BY
EXTRACTING SQUARE ROOT
Recall that a second-degree equation in
one variable is an equation that can be
expressed in the form
ax2 + bx + c = 0
Where a, b, and c are real numbers, and a ≠ 0.
This form of the quadratic equation is said to be
in standard form since all the nonzero terms are
on the left side of the equation and appear in
the order of descending powers of the variable.
There are two classifications of quadratic
equations in two variables according to the
value of b in standard form.
If b≠0, the equation is a complete
quadratic equation. Examples of complete
quadratic equations are
X2 -4x +1 = 0 and 3x2 + 2x -1 = 0
If b = 0, the equation is a pure or incomplete
quadratic equations. For instance,
X2 -9 = 0 and 3x2 + 6 = 0
Are incomplete quadratic equations.
Note that the incomplete quadratic equation
X2 - 9 = 0 can be written as X2= 9. By
substitution, two values of x satisfy this
equation. These are 3 and -3.
To check, if X2 - 9= 0 and x = 3,
32 – 9 = 0
9-9 = 0
0 =0 True

If x2 – 9 = 0 and x = -3,
(-3)2 – 9 = 0
9 -9 = 0
0=0 True
Note that √9 = 3 or √9 = -3
As a general rule, to solve equations of the
form X2 = n, use the Square Root Property.
Square Root Property: If X2 = n, then x = √n or
x = -√n
Example 2. Solve the equation (x +4) 2 = 1.
Solution:
(x +4) 2 = 1
√ (x +4) 2 = √1
x +4 = ±1
For x +4 = 1
X = -3
To check: If x = -3
(-3+4) 2 = 1
(1) 2 = 1
1=1 true
For x +4 = -1
X = -5
To check: If x = -5
(-5+4) 2 = 1
(-1) 2 = 1
1=1 true
The solutions are -3 and -5.
Note that the examples above show two
solutions to these equations. This is in fact
true to all quadratic equations.

Number of Solutions in a Quadratic Equation

Every quadratic equations in one


variable has exactly two solutions or roots.
B. SOLVING QUADRATIC
EQUATIONS BY
FACTORING
If the left side of a complete quadratic in standard
form can be factored into two linear factors, the
roots or solutions of the quadratic equation can be
obtained quickly and easily.
Recall that the test for factorability of a trinomial of
the form ax2 + bx +c states that if the discriminant
D = b2 -4ac is a perfect square, then the trinomial
is factorable.
For instance, the trinomial x2 -8x +12, where a=1,
b= -8, and c=12 is factorable since
D = b2 -4ac
= (-8) 2 – 4(1)(12)
= 64 – 48
= 16 or 42
is a perfect square
In fact,
X2 – 8x +12 = (x -6) (x-2)

However, the trinomial 2x2 -13x +12, where a=2,


b=-13, and c= 12 is not factorable since
D = b2 -4ac
= (-13) 2 – 4(2)(12)
= 169 – 96
= 73
Is not a perfect square.
Example 1. Solve x2 + 5x + 6 = 0.
This equation is already in the form "(quadratic)
equals (zero)"
So the first thing I have to do is factor:
x2 + 5x + 6 = (x + 2)(x + 3)
Set this equal to zero:
(x + 2)(x + 3) = 0
Solve each factor: x + 2 = 0 or x + 3 = 0
x = –2 or x=–3
The solution to x2 + 5x + 6 = 0 is x = –3, –2
Checking x = –3 and x = –2 in x2 + 5x + 6 = 0:
[–3] 2 + 5[–3] + 6 = 0
9 – 15 + 6 = 0
9 + 6 – 15 = 0
15 – 15 = 0
0=0
[–2] 2 + 5[–2] + 6 = 0
4 – 10 + 6 = 0
4 + 6 – 10 = 0
10 – 10 = 0
0=0
So both solutions "check".
Example 2. Solve x2 – 3 = 2x.
This equation is not in "(quadratic) equals (zero)"
form, so I can't try to solve it yet. The first thing I
need to do is get all the terms over on one side,
with zero on the other side. Only then can I factor
and solve:
x2 – 3 = 2x
x2 – 2x – 3 = 0
(x – 3)(x + 1) = 0
x – 3 = 0 or x + 1 = 0
x = 3 or x = –1
Then the solution to x2 – 3 = 2x is x = –1, 3
Checking x = –1 and x = 3 in x2 – 3 = 2x:
If x = -1
[–1] 2 - 3 = 2[-1]
1 -3= -2
-2 =-2
If x = 3
[3] 2 - 3 = 2[3]
9 -3= 6
6 =6
So both solutions "check".
Example 3. Solve 3x2 = 2x.
Solution:
Since x may be any real number (including 0), do not
attempt to divide both sides of the equation by x.
Instead, use Addition Property of Equality. Make one
side ) by subtracting 2x from both sides. Then, factor
the left side.
3x2 = 2x
3x2 - 2x = 0
x(3x - 2) = 0
X = 0 or 3x - 2 = 0
X = 2/3

Hence, the solutions are x = 0 and x = 2/3


C. SOLVING QUADRATIC
EQUATIONS BY
COMPLETING THE SQUARE
A quadratic equation in standard form is easily
solved when its left side is factorable. But the
problem arises when it cannot be factored. A
different method is required for such case. One
method of solving quadratic equations that works
whether the equations can be factored or not is the
method of completing the square.
The main task in using the method of
completing the square is to produce a perfect
square trinomial (PST) on the left side of the
quadratic equation, then use the Square Root
Property to solve the equation.

To make an expression of the form x2 + bx, a


perfect square trinomial, and add (1/2b) 2 to it.
Example 1. What will be added to expression
x2 + 4x to make it a perfect square trinomial.
Factor the resulting trinomial.
Solution:
In the expression x2 + 4x, b = 4
1/2(b) = ½ (4) =2
(1/2b)2 = [½(4)] 2 = 4
Hence, add 4 to x2 + 4x to make it a Perfect
Square Trinomal
x2 + 4x + 4= (x + 2)2
EXAMPLE 2: Solve x2 + 6x + 8 = 0 by completing the
square.
Solution:
This is a case where a= 1.
x2 + 6x + 8 = 0 Given
x2 + 6x = -8 Make the left side free of the
constant term
x2 + 6x + 9 = -8 + 9 Making the left side a
Perfect Square Trinomial
(PST); applying Addition
Property of Equality
(x + 3) 2 = 1 Factoring the PST and
simplifying
the right side
√ (x + 3)2 = ± √1 Applying Square Root
Property
x + 3 = ±1 Extracting the square root of
both sides
x = -3 ± 1 solving for x
x = -3 + 1 = -2 or
x = -3 -1 = -4
Thus, the solution to the equation are -2 and -4.
Example 3. Use completing the square to solve
x2 – 4x – 8 = 0.
As noted above, this quadratic does not factor, so I
can't solve the equation by factoring. And they
haven't given me the quadratic in a form that is ready
to square-root. But there is a way for me to
manipulate the quadratic to put it into that form, and
then solve. It works like this:
First, I put the loose number on the other side of the
equation:
x2 – 4x – 8 = 0
x2 – 4x = 8
Then I look at the coefficient of the x-term, which is –
4 in this case. I take half of this number (including the
sign), giving me –2. Then I square this value to get
+4 or in other word add (1/2b) 2 , and add this
squared value to both sides of the equation:
x2 – 4x + 4 = 8 + 4
x2 – 4x + 4 = 12
This process creates a quadratic that is a perfect
square, and factoring gives me:
(x – 2)2 = 12
(I know it's a "minus two" inside the parentheses
because half of –4 is –2. If you note the sign when
you're finding one-half of the coefficient, then you
won't mess up the sign when you're converting to
squared-binomial form.)
Now I can square-root both sides of the equation,
simplify, and solve:
(x – 2)2 = 12

Then the solution is

Then the solution is x = 2± 2√3


D. SOLVING QUADRATIC
EQUATIONS BY USING THE
QUADRATIC FORMULA
The Quadratic Formula:
For ax2 + bx + c = 0, the value of x is given by:
The nice thing about the Quadratic Formula is that the
Quadratic Formula always works. There are some
quadratics (most of them, actually) that you can't
solve by factoring. But the Quadratic Formula will
always spit out an answer, whether the quadratic was
factorable or not.
Let's try that last problem from the previous section
again, but this time we'll use the Quadratic Formula:
Example 1. Use the Quadratic Formula to solve
x2 – 4x – 8 = 0.
I should get the same answer as before:(using
Solving Quadratic Equations by completing the
square)
Using the quadratic formula
Solution:
The given equation, x2 – 4x – 8 = 0, is in standard
form, and a=1, b= -4, and c= -8.
Using the quadratic formula

X = -(-4) ± √(-4)2 – 4(1)(-8)


2(1)

X = -(-4) ± √16 + 32
2(1)
X = 4 ± √48
2
X = 4 ± √16(3)
2
X = 4 ± 4 √3
2
X = 2± 2√3

Then the solution is 2± 2√3


Example 2. Use the Quadratic Formula to solve
2x2 – x – 1 = 0.
Solution:
The given equation is in standard form, and a=2, b= -1,
and c= 1.
Using the quadratic formula
X = -b ± √b2 – 4ac
2a
X = -(-1) ± √(-1) 2 – 4(2)(-1)
2(2)
X = 1 ± √1 + 8
4
X = 1+ √9
4
X=1±3
4
X = 1+ 3
4
X=1
Or
X = 1- 3
4
X = -1/2
Thus, the solutions are 1 and -1/2
Example 3. Solve for x in x2 – 6x + 9 = 0.
Solution:
The given equation is in the form ax2 + bx + c = 0, and
a= 1, b = -6, and c= 9.
Using the Using the quadratic formula
X = -(-6)± √(-6)2 – 4(1)(9)
2(1)
X = 6 ±√0
2
X = 6/2 or 3
Thus, the solution of the given equation is 3.
Notice that there is only one value of x as solution.
When the given quadratic equation is solved by
factoring, the result will be.
x2 – 6x + 9 = 0
(x-3) (x-3) = 0
X -3 = 0 or X -3 = 0
X = 3 or x = 3
The two solutions of the given equation are equal.
Thus, there is only one value of x derived using the
quadratic formula. It is said that the solution x = 3
is a double root.
Thank you!